Post exposure prophylaxis uptake against exposure to HIV/AIDS risk factors in healthcare settings was very low - Kebede Beyera, Getahun; Haile Chercos, Daniel (International Journal of Infection Control, 2015)
On the already limited human resource capacity in health care workforce, HIV is also causing loss of health professionals. Africa, in particular, faces the loss of vast numbers of educated health care workers. Given the pivotal role of frontline health care workers in resource constrained countries, the potential loss of this number of health care workers each year is a serious problem that needs urgent attention The aim of this study was to evaluate post-exposure prophylaxis utilization against exposure to HIV/AIDS risk factors among health care workers in Gondar city, Northwest Ethiopia. Institution based quantitative cross-sectional study was conducted from May 5-26, 2014 in one referral hospital and three health centres in Gondar city. A total of 162 health care workers having history of occupational exposure to HIV/AIDS risk factors within the last one year were selected through simple random sampling method. Data collected by interviewing health care workers were entered using EPI INFO version 3.5.3 statistical software and exported to and analyzed using SPSS version 20.0. From a total of 162 health care workers having occupational exposure to HIV/AIDS risk factors, only 41 (25.3%) received post exposure prophylaxis. Gender, reporting occupational exposure and drinking alcohol were significant factors associated with post exposure prophylaxis uptake by health care workers against accidental occupational exposure to HIV/AIDS risk factors. The great majority of health care workers fail to utilize HIV post exposure prophylaxis following accidental exposure to HIV/AIDS risk factors, which leads to a high occupational risk of HIV/AIDS infection. Thus, there is a need for provision of training on infection prevention and development of guidelines outlining reporting mechanism and procedure to be followed for post exposure prophylaxis and follow-up testing.